HUBUNGAN FAKTOR IBU DENGAN KEMATIAN BAYI DI KABUPATEN BIMA - Rini Hendari (poltekkes kemenkes mataram, 2014)
: Infant mortality was death of a child before the age of one year, can be caused by endogenous and exogenous factors. One of the factors associated with infant mortality are factors include: age of mother, spacing births, exclusive breast feeding and maternal knowledge about infant care. The purpose of this research was to the know the related factors of the mother with the infant mortality.This type of research is observational analytic, with a case-control study, which is the case of infant mortality in the period January to December 2012 and control infant live on same period. Case and control were selected in Bima Regency society through way of stratified proportional sampling wich totaled 153 respondents with a ratio 0f 1 to 2. Data was collected through questionnaires and interviews with midwives registers documentation. Data analysis using Chi Square test. The result analysis was obtained of OR not exclusively breastfeeding by 4,79 (95% CI 2.21 – 10.39 ) with p=0.000, OR: 5,33 spacing births <24 months, (95% CI 2.30 – 12.37), p=0.000, maternal age < 20 or >35 years OR=4,13 (95% CI 1.76 – 9.72), p=0.001 and maternal knowledge the less about infant care OR; 6,77: 95 % ( el 3.19 – 14.35 ), p=0,000. According to the research is concluded that is not exclusively breastfeeding, spacing births <24 months, maternal age <20 or >35 years and maternal knowledge the less about infant care related to infant mortality. Suggestions on improving the supervision and monitoring of the activities of clinics-puskesmas KIE/extension and promotion of the importance of the delay the age of marriage, spacing pregnancies. Exclusive breast feeding up to 6-month-old baby.